Analisis Perbandingan Metode SAW dan Metode Topsis melalui Pendekatan Uji Sensitivitas Penilaian Kinerja Pegawai (Studi Kasus : Dinas Perhubungan Bengkulu Tengah) - Setiawan, Gana Wahyu; Wahyudi, Jusuf; Sudarsono, Aji (LPPM UNIKA Santo Thomas Medan, 2022)
So far, employee performance appraisals at the Central Bengkulu Transportation Service have used a predetermined form. Seeing the way in conducting employee performance appraisals that are still manual, a decision support system is needed so that employee performance appraisals get an accurate assessment. The method that can be applied in conducting the assessment is the SAW method and the TOPSIS method as well as conducting a sensitivity test for evaluating employee performance, sensitivity testing is the process of knowing and getting results from the comparison of the two methods. The results of the assessment are 10 employees with the SAW method ranking 1, namely Zainal Arifin with a total score of 35, ranking 2 Yosi Eskamarina with a total value of 31 and ranking 3 Donny Irawan with a total value of 29. While the assessment uses the TOPSIS method, namely ranking 1 Zainal Arifin with a total value of 1.00, ranking 2 Donny Irawan with a total score of 0.68, and rank 3 Yosi Eskamarina with a total score of 0.29. With the sensitivity test based on the employee's performance assessment, it is expected to be able to determine the right method between the saw method and the topsis method.